Attitudes and Personal Attributes Regarding Patient Receptivity towards the Participation of Medical Students in Gynecological Consultations: A Cross-Sectional Study - Wanderley, Miriam da Silva; Sobral, Dejano Tavares; Lima, Brenda Alves de Oliveira; Freire, Maria Elisa de Bessa; Silva, Mariana Albuquerque Campos da; Rosa, Marina Prado e Silva Gonçalves; Souza, Thaís Ferreira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Objective To evaluate the association between the acceptance on the part of the patients and their reasons to consent to or refuse medical student attendance during gynecological outpatient care, considering the participants' demographic characteristics, consultation experience, and gender bias or lack thereof.Methods Face-to-face interviews with patients waiting for gynecological consultations that had been scheduled in advance at Hospital Universitário de Brasília. Contingency analyses were used to determine the levels of association among the patient variables. The accepted significance level was values of p < 0.05.Results We interviewed 469 patients. The comfort level with the presence of a student was strongly related to the number of students present during the consultation (Cramér V = 0.671). The inclination to grant consent (a series of reasons to consent to or refuse student attendance) was significantly related (p < 0.001) to the overall receptivity to student participation (ρ = 0.482), the positive appraisal of student-doctor demeanor in previous consultations (ρ = 0.253, N = 408), and to greater levels of schooling (ρ = 0.158). The patients' receptivity was significantly related (p < 0.001) to the lack of bias regarding the gender of the physician (Cramér V = 0.388), previous experience with students (Cramér V = 0.235) and awareness of the fact that they would be present (Cramér V = 0.217), older age (ρ = 0.136, p = 0.003), and multiparity (ρ = 0.102, p = 0.027).Conclusion Greater receptivity to student participation related significantly to five conditions in decreasing order of strength of association: lack of bias regarding the gender of the Ob-Gyn, previous experience with student involvement, awareness of the presence of students, older age, and multiparity. We also found that a more positive inclination to consent to student attendance correlated positively with a greater receptivity to student participation and to a suitable student-doctor demeanor.
Keywords: healthcare; medical student; gender; outpatient care; gynecology